"As a woman who watches how my family is... I take the difficult decisions": a qualitative study on integrated family planning and childhood immunisation services in five African countries - Jenna Hoyt; Shari Krishnaratne; Jessie K. Hamon; Lydia Boudarene; Tracey Chantler; Shiferaw Dechasa Demissie; Justine Landegger; Easterlina Moseti; Seth Marcus; Misozi Kambanje; Shannon Pryor; Nathaly Spilotros; et al. (BMC, 2021)
Abstract Background Family planning (FP) has the potential to improve maternal and child health outcomes and to reduce poverty in sub-Saharan Africa. However, substantial unmet need for modern contraceptive methods (MCMs) persists in this region. Current literature highlights multi-level barriers, including socio-cultural norms that discourage the use of MCMs. This paper explores women's choices and decision-making around MCM use and examines whether integrating FP services with childhood immunisations influenced women's perceptions of, and decision to use, an MCM. Methods 94 semi-structured interviews and 21 focus group discussions with women, health providers, and community members (N = 253) were conducted in health facilities and outreach clinics where an intervention was delivering integrated FP and childhood immunisation services in Benin, Ethiopia, Kenya, Malawi and Uganda. Data were coded using Nvivo software and an analytical framework was developed to support interpretative and thematic analyses on women's decision-making about MCM use. Results Most women shared the reproductive desire to space or limit births because of the perceived benefits of improved health and welfare for themselves and for their children, including the economic advantages. For some, choices about MCM use were restricted because of wider societal influences. Women's decision to use MCMs was driven by their reproductive desires, but for some that was stymied by fears of side effects, community stigma, and disapproving husbands, which led to clandestine MCM use. Health providers acknowledged that women understood the benefits of using MCMs, but highlighted that the wider socio-cultural norms of their community often contributed to a reluctance to use them. Integration of FP and childhood immunisation services provided repeat opportunities for health providers to counter misinformation and it improved access to MCMs, including for women who needed to use them covertly. Conclusions Some women chose to use MCMs without the approval of their husbands, and/or despite cultural norms, because of the perceived health and economic benefits for themselves and for their families, and because they lived with the consequences of short birth intervals and large families. Integrated FP and childhood immunisation services expanded women's choices about MCM use and created opportunities for women to make decisions autonomously.